U.S. International Exhibitions during the Cold War : Winning Hearts and Minds through Cultural Diplomacy - Wulf, Andrew James, 1971- (Rowman and Littlefield, 2015)
Advances a new understanding of cultural diplomacy that results from an historical investigation of a single area of government and private sector partnership, and what became in the mid-twentieth century, the most promininent manifestation of this alliance--the cultural exhibitions sent abroad to "tell America's story" with the goal of "winning hearts and minds."